Parish Clergy of Voronezh Diocese in Fight Against the Cholera Epidemic of 1892—1893 - S. A. Ikonnikov (Научный диалог, 2021)
The article is devoted to the study of the role of clergy and clergymen of the Voronezh diocese in the fight against the spread of the cholera epidemic of 1892-1893. The novelty of the study lies in the fact that the contribution of the clergy of the Orthodox Russian Church to countering the spread of infectious diseases has practically not been studied. It is noted that in the Russian Empire, Orthodox clerics were not only ministers of the altar, but also performed a number of socially significant functions. Based on a wide range of historical sources, the author analyzes the attitude of the population of the Voronezh province to cholera disease. The educational activity of clerics, the participation of clergy in organizing aid to parishioners are considered. It is emphasized that the clergy were closely associated with the peasant population of the empire, daily contact with them during the divine service. The study showed that the state tried to use the experience and knowledge of the clergy and clergymen, considering them as the social support of the autocratic system. The author concludes that the parish clergy and clergymen played an important role in the fight against infectious disease, not only participating in educational activities and spiritually supporting the population, but also providing those in need with initial medical assistance.